1988
DOI: 10.1136/bmj.297.6654.958
|View full text |Cite
|
Sign up to set email alerts
|

Wholemeal versus wholegrain breads: proportion of whole or cracked grain and the glycaemic response.

Abstract: Study objective-To determine the effect on the glycaemic response to bread of the ratio of whole cereal grains to milled flour.Design-Randomised assignment of groups of diabetic volunteers to test and control meals, taken after an overnight fast. Test foods were also analysed for in vitro digestion with human saliva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(119 citation statements)
references
References 17 publications
4
111
0
4
Order By: Relevance
“…Another potential mechanism is to slow down starch digestion and absorption, which leads to lower glucose and insulin responses that favour oxidation and lipolysis of fat rather than its storage (Slavin et al, 1999). Diets rich in whole-grain products have a low glycaemic index (GI) (Jenkins et al, 1986(Jenkins et al, , 1988. Several studies have investigated the effect of low compared to high glycaemic diets on weight gain or reduction (reviewed in Ludwig, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential mechanism is to slow down starch digestion and absorption, which leads to lower glucose and insulin responses that favour oxidation and lipolysis of fat rather than its storage (Slavin et al, 1999). Diets rich in whole-grain products have a low glycaemic index (GI) (Jenkins et al, 1986(Jenkins et al, , 1988. Several studies have investigated the effect of low compared to high glycaemic diets on weight gain or reduction (reviewed in Ludwig, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Wholemeal bread does not appear to have a lower GI than white bread (GI of 70 relative to glucose), despite its much higher fibre content (FosterPowell et al, 2002). This is due to the absence of whole-grain kernels in bread (Jenkins et al, 1988); actually, in the majority of Dutch wholemeal or brown breads, the fibrerich fraction is added back to the white flour after removal of the germs to prolong shelf life. The whole-grain products eaten by our population, in contrast, have a GI varying between 40 and 60.…”
Section: Discussionmentioning
confidence: 99%
“…The former includes the ratio of amylose to amylopectin present in the raw food (Behall et al, 1988) and the type of monosaccharide components, the amount and type of dietary fiber (Jenkins et al, 1978), the presence of large amounts of fat or protein (Nuttall et al, 1984;Wolever et al, 1985;Collier et al, 1986;Bornet et al, 1987), antinutrients such as phytic acid, lectins and tannins (Yoon et al, 1983;Thompson et al, 1984;Rea et al, 1985) and nutrient -starch interactions in carbohydrate-containing foods, such as in wheat products (Jenkins et al, 1987a). Extrusion, flaking, grinding, canning, storing and cooking of the carbohydrate-containing foods can affect the particle size and the integrity of the starch granules (Jenkins et al, 1988a) and plant cell walls (Ellis et al, 1991), making the carbohydrate portion more accessible to digestive enzymes (Wolever, 1990;Collins et al, 1981).…”
Section: Glycemic Index and The Slow-release Carbohydratementioning
confidence: 99%
“…In contrast, pasta products (Granfeldt & Bjo Èrck, 1991) and certain rice display GI in the lower range (GI 45 ±70). The GI of legume products (Dilawari et al, 1981;Tovar et al, 1992) and intact cereal grains (Granfeldt et al, 1994;Jenkins et al, 1988b) have been found to be very low, and in fact among the lowest reported for starchy foods (GI 15± 65). In a few studies it has been demonstrated that the organic acids formed during fermentation of, for instance, vegetables (Torsdottir et al, 1992) and bread (Liljeberg et al, 1995) may signi®cantly improve the glucose tolerance to starch.…”
Section: Introductionmentioning
confidence: 97%